Peran Pinjaman International Monetary Funding (IMF) Untuk Perekonomian Indonesia Pada Sistem Standar Moneter - Muhammad Luis; Yasirwan; Imsar (DPPM Universitas Pelita Bangsa, 2023)
The International Monetary Fund was formed at the time of the United Nations meeting in the United States in 1944 at Bretton Woods (New Hempshire). This organization is in an international association which handles financial problems. The economic crisis hit Indonesia during President Soeharto's leadership, at that time Soeharto officially asked the International Monetary Fund for assistance in resolving the monetary and economic crisis. that from the results the researcher aims to provide further information in order to find maximum results from the previous analysis that has been carried out. The research method in this journal article is to use a qualitative method, by taking article sources through several journal references. Then the researcher inspected it and put the thoughts from the identification into this almost perfect journal. Because researchers want to clarify more about the role of international monetary fund loans in the Indonesian economy, which is based on the international monetary standard system. The research results show that the assistance provided by the International Monetary Fund only adds to the country's disasters, especially for the poor. Because Indonesia continues to carry out cooperative activities with the International Monetary Fund, because the country is still unable to pay off its debts, and it is impressed by the state's actions such as (digging holes and covering holes) in paying and paying off its debts.